Application of Digital Pattern Techniques in Ready to Wear Fashion Based on CLO3D Software - Yaumatul Mustaghfiroh; Noor Laila Ramadhani (Universitas Negeri Semarang, 2025)
Abstract. Fashion patterns serve as the basic templates for garment creation, playing a crucial role in ensuring the fit and comfort of the resulting clothing. Advances in digital technology, particularly in fashion, have significantly transformed the design and production processes. CLO3D software allows designers to create fashion patterns in a digital 3D format, which accelerates design, reduces costs, and supports sustainability by minimizing waste. This research employs the Research and Development (R&D) method to develop a user guide for using CLO3D. The research findings indicate that digital pattern techniques enhance efficiency, accuracy, and creativity in design. Validation of the user guide by experts shows a high level of validity with a consensus index of 1.0, indicating its relevance and effectiveness in learning. This study concludes that CLO3D not only improves the quality of designs but also contributes significantly to education and skill development in the fashion field.